Everyday mobility practices and the ethics of care: young women's reflections on social responsibility in the time of COVID-19 in three African cities. Issue 1 (2nd January 2023) - Porter, Gina; Dungey, Claire; Murphy, Emma; Adamu, Fatima; Bitrus Dayil, Plangsat; de Lannoy, Ariane
Abstract: This paper draws principally from COVID-19 diaries written by young women whom we had previously trained as peer researchers in a mobility study of low-income neighbourhoods in Abuja, Cape Town and Tunis. Some live with parents or older extended family members, others have children in their care, but concerns around avoiding contagion have forced all peer researchers to reflect on their everyday socio-spatial mobility practices. This includes whether/how much they need to travel or can substitute virtual for physical travel; which transport mode to take and when; what precautions they must take on the move; what strategies of engagement are required to cope with externally imposed rules and contingencies – and the potential impact of their negotiations, decisions and experiences on the health of those dear to them at home. Reflections on these pandemic-induced responsibilities range from social distancing and mask wearing to issues around handling cash, modes of greeting and travel to funerals. The personal interpretations of responsibility that are reported in individual diaries point to the complexity of entanglements between everyday mobility practices on city streets and negotiated relations of care within the household (and other relational settings) that have emerged and deepened as the COVID story unfolds.